The ancient Greek roots of human rights - Sternberg, Rachel Hall (University of Texas Press, 2021)
"A work of intellectual history, the book traces the notion of human rights as articulated in the Enlightenment to the evolution of humane discourse and empathetic thought in Ancient Greece"--